PENGEMBANGAN KAWASAN WISATA BEKAS GALIAN SEBAGAI UPAYA PENGEMBANGAN EKONOMI DAN KONSERVASI: Tempat wisata galian Subang - Kharisma, Lutfiandina; Juwita, Tita (Jurnal Perhotelan dan Pariwisata, 2023)
The former mining quarry sites in the Subang Regency's Cipendeuy district are frequently visited by tourists to be developed as tourist destinations, even though the area is predominantly industrial. These former mining quarry sites hold significant economic value and ecological quality, provided they are well managed by the Subang Regency government. This aligns with the flagship program named 'Jawara Wisata' (Tourism Champion), which supports tourism development in Subang Regency. The facilities within the tourist area need to be developed concerning the management of the area's facilities. It is also hoped that these former quarry sites can become a source of livelihood for the local community. This research aims to determine the economic value of the area as a tourist destination. Revitalization efforts are necessary for these former quarry sites. Therefore, data collection methods involve conducting surveys. This survey technique includes sampling and direct interviews with respondents to identify the potential and socio-economic conditions related to resource utilization